Modelling of the VU budget means alocation - Pikturna, Aleksas; Ivanauskas, Feliksas; Lapcun, Bogdan (Lietuvos matematikos rinkinys, 2002)
Quantitative tools for the budget in higher education have appeared in great number in last decade of last century. Two approaches of the mathematical modelling have appeared in higher education: the package model and locally designed model. Package models employ generalized relationships that are applicable to behavior in many different settings. These models seems to be the least utilized of the quantitative tools. Locally designed models simulate behavior or a process in a specific setting. This paper analyze one locally designed model – Vilnius University budget allocation (among departments) model. Calculations have been made using data of Vilnius University administration.